2016
DOI: 10.18632/oncotarget.9790
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pancreatic cancer in a hamster model by cAMP decrease

Abstract: Smoking and alcoholism are risk factors for the development of pancreatitis-associated pancreatic ductal adenocarcinoma (PDAC). We have previously shown that these cancers overexpressed stress neurotransmitters and cyclic adenosine monophosphate (cAMP) while the inhibitory neurotransmitter γ-aminobutyric acid (GABA) was suppressed. Using a hamster model, the current study has tested the hypothesis that cAMP decrease by GABA supplementation in the drinking water prevents the development of pancreatitis-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In prokaryotes, cAMP may directly activate RNA polymerase in order to promote its transcription, through the 6-factor phosphorylation level of the enzyme, to promote the transcription level of RNA. Recent studies demonstrated that the role of cAMP in eukaryotic cells was determined to be associated with regulation of transcription factors (77,78), for example, gene expression patterns define key transcriptional events in cell-cycle regulation by cAMP and protein kinase A. cAMP has the effect of inhibiting its cell division and promoting cell differentiation (41,42). cAMP also has a dual effect on cell proliferation, which promotes cell proliferation at early G0 or G1, and is inhibited at late G1 (42).…”
Section: Discussionmentioning
confidence: 99%
“…In prokaryotes, cAMP may directly activate RNA polymerase in order to promote its transcription, through the 6-factor phosphorylation level of the enzyme, to promote the transcription level of RNA. Recent studies demonstrated that the role of cAMP in eukaryotic cells was determined to be associated with regulation of transcription factors (77,78), for example, gene expression patterns define key transcriptional events in cell-cycle regulation by cAMP and protein kinase A. cAMP has the effect of inhibiting its cell division and promoting cell differentiation (41,42). cAMP also has a dual effect on cell proliferation, which promotes cell proliferation at early G0 or G1, and is inhibited at late G1 (42).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study revealed that blocking cAMP-dependent intracellular signalings may prevent the development of pancreatic cancer. It was also found that the development of pancreatic cancer was prevented by cAMP decrease in hamster models [ 37 , 38 ]. However, few studies have been reported to directly focus on the role of cAMP in migration and invasion of pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies that have employed agonists of receptors coupled to the inhibitory G-protein G i (GABA-B receptors, opioid peptide receptors) for the inhibition of β-AR-mediated progression of adenocarcinoma of the lungs and pancreas in vitro and in vivo have repeatedly shown that increases in intracellular cAMP and the associated activation of its downstream effectors are key molecular events that activate β-AR-driven development and progression of both cancers and can be successfully inhibited by agonists of G i -coupled receptors that inhibit the formation of cAMP by blocking the activation of adenylyl cyclase. [41,42,51,54,55,66,[74][75][76] A host of non-β-AR receptors coupled to the stimulatory G-protein G s increase intracellular cAMP, [3,77] a reaction not inhibited by beta-blockers but effectively counteracted by agonist-induced signaling of G icoupled receptors. There is also a host of non-betaadrenergic agents that increase intracellular cAMP directly.…”
Section: Discussionmentioning
confidence: 99%
“…[48,49] GABA is the main inhibitory neurotransmitter in the mammalian body and inhibits the AC-dependent formation of cAMP as well as the activation of voltage-gated Ca 2+channels [50] under physiological conditions by activating inhibitory G-protein (G i ) signaling downstream of G icoupled GABA-B-receptors. In light of findings that the GABA-B receptor has tumor suppressor function in pancreatic [42,[51][52][53] and non small-cell lung cancer (NSCLC) [35,41,54,55] while GABA also inhibits the in vitro growth of breast cancer and colon cancer, [47,56] suppression of GABA by psychological stress has significant tumor promoting effects on these cancers.…”
Section: Introductionmentioning
confidence: 99%